Crystal structure and Hirshfeld-surface analysis of an etoxazole metabolite designated R13 - Thaluru M. Mohan Kumar; Besagarahally L. Bhaskar; Prabhakar Priyanka; Thayamma R. Divakara; Hemmige S. Yathirajan; Sean Parkin (Acta Crystallographica Section E: Crystallographic Communications)
The etoxazole metabolite R13, systematic name 4-(4-tert-butyl-2-ethoxyphenyl)-2-(2,6-difluorophenyl)oxazole (C21H21F2NO2), results from the oxidation of etoxazole, a chitin synthesis inhibitor belonging to the oxazoline class, widely used as an insecticide/acaricide since 1998. The structure of R13 features a central oxazole ring with attached 2,6-difluorophenyl and 4-t-butyl-2-ethoxyphenyl moieties. The overall conformation gives dihedral angles between these rings and the oxazole of 24.91 (5)° (with difluorophenyl) and 15.30 (6)° (with t-butyl-ethoxyphenyl), indicating an overall deviation from planarity. Additionally, torsion angles of the ethoxy and t-butyl groups define the orientation of these substituents relative to their benzene ring. In the crystal packing, no significant hydrogen bonds are present, but a Hirshfeld surface analysis highlights weak intermolecular contacts leading to π–π-stacked dimers linked by weak C—H...N contacts. The packing analysis confirms that most intermolecular interactions involve hydrogen atoms.